2018
DOI: 10.1097/md.0000000000013266
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus nonsurgical treatment for scaphoid waist fracture with slight or no displacement

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 63 publications
3
12
1
Order By: Relevance
“…2 Immediate surgical fixation is said to avoid the need for a cast and accelerate return to function, work, and sport 7 but exposes patients to surgical risks. Eight small randomised clinical trials in United Kingdom, United States of America (USA) and Sweden, 8 of variable quality, reporting on undisplaced or minimally displaced fractures of the scaphoid waist, provide unclear evidence on whether surgical fixation gives better outcomes than cast immobilization. Despite insufficient evidence there is an increasing trend 9 to immediately fix this fracture for perceived short-term benefits, but concerns remain about the lack of evidence on long-term benefits and additional risks from surgery, such as malunion, infection, and implant related problems.…”
Section: Introductionmentioning
confidence: 99%
“…2 Immediate surgical fixation is said to avoid the need for a cast and accelerate return to function, work, and sport 7 but exposes patients to surgical risks. Eight small randomised clinical trials in United Kingdom, United States of America (USA) and Sweden, 8 of variable quality, reporting on undisplaced or minimally displaced fractures of the scaphoid waist, provide unclear evidence on whether surgical fixation gives better outcomes than cast immobilization. Despite insufficient evidence there is an increasing trend 9 to immediately fix this fracture for perceived short-term benefits, but concerns remain about the lack of evidence on long-term benefits and additional risks from surgery, such as malunion, infection, and implant related problems.…”
Section: Introductionmentioning
confidence: 99%
“…7 Ibrahim et al and Li et al found similar results in their meta-analyses, suggesting better outcomes with open fixation versus nonsurgical management, while there was no significant difference in union rates with percutaneous versus nonsurgical management. 4,5 Overall, these studies suggest that the assumption that open techniques are superior to percutaneous approaches is not empirical and requires more investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Low complication rates and high rates of union with open and percutaneous fixation of the scaphoid have been documented in numerous studies. 2,4,5,7 When compared with percutaneous techniques, open fixation provides the benefit of better visualization of the starting point of the central axis guidewire. 15 This visual advantage does allow some surgeons to be more accurate with guidewire and screw placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Closed reduction and percutaneous fixation with different types of cannulated screws under fluoroscope is nowadays gaining popularity because it shortens the time to union and convalescence. 20 Anyhow, chronic waist fractures may need open reduction and bone grafting along with stable fixation for early range of motion. Even small sized distal pole fractures which are neglected and symptomatic can be excised.…”
mentioning
confidence: 99%